Sosialisasi Pendampingan Hukum Terhadap Anak Asuh di SOS Children Villages - Nila Trisna (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Law No. 35 of 2014 concerning protection of children also guarantees the fulfillment of children's rights to survival, growth and development and is entitled to protection from violence and discrimination. Fulfillment of the rights of basic needs and protection for children in the scope of West Aceh has not yet been fully implemented. The process of conducting the socialization was carried out by the method of exposure and discussion of legal counseling materials about the role and obligations of the Government in providing legal protection to children who need legal assistance. The participation of all parties in paying attention to the protection of children is one thing that is very urgent. Given cases involving children in conflict with the law both as perpetrators and victims, often ignoring the rights of children who should be protected by laws and regulations. This is what needs to be done by all parties to encourage the West Aceh District Government to immediately give birth a Qanun on Child Protection. So that with regulations specifically related to child protection, children's rights are guaranteed by law.